Answer:
A. (x - 10)(x - 4)
Step-by-step explanation:
Let x=4
O A. (4 - 10)(4 - 4) = -6 * 0 = 0
OB. (4 + 4)(4 - 10) = 8* -6 = -48
O C.(4 + 6)(4 - 2) = 10 * 2 = 20
OD. 4*4(4-6)=16*-2 = -32
Answer:
A. (x - 10)(x - 4)
Step-by-step explanation:
The product is 0 if one of the factors is 0.
(4 - 10)(4 - 4)
= (4 - 10)*0
= 0
Y = x^2 + 5x - 17
Y = x - 5
Answer:
2
Step-by-step explanation:
What you could do is fill in 2 for the equation and y would equal -3 so for the first one it's like
y= 2^2 + 5(2) -17
y= 4 + 10 - 17 which turns into y= -3
In the second y it would be something like
y= 2 - 5 which would equal y= -3
so x=2
4 hours of
loading/unloading
7 hours of
loading/unloading
Step-by-step explanation:
Here, the given table is MISSING.
The correct table for reference is attached.
Now, let us assume the hourly rates of loading/unloading = $ m
Assume the hourly rates of packing/unpacking = $ n
As given in the table:
3 hours of loading/unloading + 2 hours of packing/unpacking costs = $480
⇒ 3 m + 2 n = 480
⇒ 2 n = 480 - 3 m .... (1)
5 hours of loading/unloading + 2 hours of packing/unpacking costs = $680
⇒ 5 m + 2 n = 680
⇒ 2 n = 680 - 5 m .... (2)
Now, solving for the values of m and n, we get:
480 - 3 m = 680 - 5 m
⇒ 5 m - 3 m = 680 - 480
⇒ 2 m = 200
or, m = 100
Now, 2 n = 680 - 5 m = 680 - 5 (100) = 180
⇒ n = 90
Hence, the hourly rates of loading/unloading = $ m = $100
The hourly rates of packing/unpacking = $ n = $90
Answer:
Step-by-step explanation:
(48-3x)>6x-8
48-3x>6x-8
Collecting like terms, we have
-3x-6x>-8-48
Moving variables or numbers from one side to the other changes the sign it carries
-9x>-56
Divining both sides by -9 changes the inequality sign
x<56/9
x<6.22
The value of the solution after subtraction is,
⇒ 4 3/5
We have to give that,
An expression to solve,
⇒ 6 1/2 - 1 9/10
Now, change the fraction into an improper fraction,
⇒ 6 1/2 - 1 9/10
⇒ 13/2 - 19/10
⇒ 65/10 - 19/10
⇒ (65 - 19) / 10
⇒ 46/10
⇒ 23/5
⇒ 4 3/5
Hence, the Solution of the fraction is. 4 3/5
To learn more about the fraction visit:
#SPJ6
Answer:
what do you need help with?
Step-by-step explanation:
Answer:
3x4x9x21=
Step-by-step explanation:
(–4, 5) and (4, –5)
(–3, 4) and (2, 0)
(1, –1) and (6, –5)
(2, –1) and (10, 9)
Answer: Im pretty sure it answer options 1 and 5
Step-by-step explanation: 1) (-2,0) and (2,5) 5) (2,-1) and (10,9)
its on edg.